2021
DOI: 10.3389/fcell.2021.750022
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Talk Between Tumor Cells Undergoing Epithelial to Mesenchymal Transition and Natural Killer Cells in Tumor Microenvironment in Colorectal Cancer

Abstract: Tumor cells undergoing epithelial to mesenchymal transition (EMT) and immune cells in tumor microenvironment (TME) reciprocally influence each other. Immune cells, by supplying TME with bioactive molecules including cytokines, chemokines, enzymes, metabolites, and by physical interactions with tumor cells via their receptors, represent an important factor that affects EMT. Chronical inflammation in TME favorizes tumor growth and invasiveness and stimulates synthesis of EMT promoting transcription factors. Natu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 153 publications
(211 reference statements)
0
18
0
Order By: Relevance
“…Both inflammation and EMT are correlated with tumour aggressiveness and poor prognosis in cancer patients. Inflammatory cytokines can activate transcription factors that drive EMT [ 18 , 19 ]. In our previous study, we identified that Wip1 suppresses metastasis in ovarian cancer through AKT/snail-mediated EMT.…”
Section: Discussionmentioning
confidence: 99%
“…Both inflammation and EMT are correlated with tumour aggressiveness and poor prognosis in cancer patients. Inflammatory cytokines can activate transcription factors that drive EMT [ 18 , 19 ]. In our previous study, we identified that Wip1 suppresses metastasis in ovarian cancer through AKT/snail-mediated EMT.…”
Section: Discussionmentioning
confidence: 99%
“…In the presence of DNA damage response failure, mismatch repair defects, and oncogene-induced replication stress, the coexistent inflammatory process can exacerbate the genetic burden and accelerate tumorigenesis through NF-κB-mediated cytokine production [ 9 ]. The semi-local inflammation promotes the accumulation of chemokines, immune cells, stromal cells, and extracellular matrix proteins, which under favorable conditions provide the foundation for the development of the tumor-supportive microenvironment [ 36 ].…”
Section: Inflammation In the Pathways Of Sporadic And Colitis-associa...mentioning
confidence: 99%
“…TIME is composed mostly of myeloid-derived stem cells and regulatory T cells, which mediate local immunosuppression, and cytotoxic T lymphocytes (CTLs), Th2 cells, and macrophages M2, which possess very restricted antitumor activity [ 41 , 42 ]. During the progression of the disease, cancer cells change the properties of surrounding cells, forcing them to produce growth factors and proinflammatory cytokines, such as TNF-α, IL-1β, and TGF-β, that accelerate the acquisition of a mesenchymal-like phenotype during EMT [ 36 ].…”
Section: Cytokines Tumor Microenvironment and Epithelial–mesenchymal ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Stress-induced signals on tumor cells can trigger NK cell activity and cytotoxicity. However, in late stage cancers, the capacity of NK cells to control tumor growth can be impaired either by antigen loss or a down regulated expression of activatory receptors induced by an immunosuppressive TME ( 24 , 25 ). An ex vivo stimulation of NK cells under optimal culture conditions up-regulates the expression of activating receptors (e.g., C-type lectin receptors, natural cytotoxicity receptors, NCRs) and thereby promotes anti-tumor immunity ( 26 , 27 ).…”
Section: Introductionmentioning
confidence: 99%